Dialogue Politeness of Prophet Abraham ( peace be upon him) with his father in the Quran chapter of Marium - عبد اللّطيف أحمد يعقوب محمّد (White Nile Journal for Studies and Research, 2023)
This research paper discusses the dialogue between the prophet Abraham( peace be upon him) and his father as revealed in the Quran chapter of Marium. Prophet Abraham convincingly attacked his father's argument and prioritized matters well. The research aimed to explain the importance of polite dialogue in Islamic invitation. The researcher used the descriptive analytical method for data collection and analysis. The study has come out with the following most important results: a person in a dialogue should be wise enough and decent enough and seek to convince others by using strong evidence. a person in a dialogue should respect others and avoid underrating them . Based on the results above, the study forwards the following recommendations: school syllabus should involve developing students' capabilities in using evidence in dialogue , it is important to take and learn lessons from these tales. parents should bring up children using wisdom and polite dialogue